Organizational climate practices in absorptive capacity: an analysis from the textile industry - Trentin, Luciano (Revista de Administração da UFSM, 2023)
Purpose: This article aims to analyze the influence of the organizational climate on the absorptive capacity. Design/Methodology/approach: The survey is characterized as descriptive and quantitative. The employed method is a survey, applied through the virtual platform Google Forms. The sample consisted of 172 respondents from five manufacturing units of a textile industry, being collected by accessibility and convenience. Multiple regression analysis was used to process and analyze the data. Findings: The research shows that hypotheses H1a, H1c and H1d are confirmed, a favorable organizational climate influences the absorptive capacity through proper management of internal relationships, effective leadership, and renowned organizational image. On the other hand, the H1b hypothesis was rejected, organizational climate did not show interference in the absorptive capacity through professional development in the confirmatory test. Originality/relevance: The significance and contribution of this study lie in addressing an observed gap in the analysis and evaluation of absorptive capacity. Specifically, it explores how organizational climate management practices interrelate with this concept, thereby shedding light on related themes. Practical implications: The study allows managers of organizations to understand which organizational climate management practices should be prioritized in the absorptive capacity, thus contributing to the creation of an environment conducive to the transfer of knowledge, that is, combining prior knowledge with the new knowledge.